Empowering The Quality Of Education To Improve The Quality And Quantity Of Human Resources Towards Era 5.0 - Sofiatul Islah, Risqi; Rizqiyana (JIEMAN: Journal of Islamic Educational Management, 2025)
The quality of education in preparing human resources to face Era 5.0, not only demands technological competence, but also high adaptability in responding to digital and industrial transformation. This research integrates literature analysis with a Qualitative approach with a type of direct study involving educational institutions that have initiated innovations in learning approaches and curriculum development. Data was collected through in-depth interviews with teachers, students as well as through observation and documentation. The study revealed that several key elements play an important role in improving the quality of education, including adaptive curriculum development, continuous professional development for educators, integration of educational technology, and active collaboration between educational institutions and local industries. These efforts are not only instrumental in improving learning outcomes, but are also crucial in aligning education with industry needs. In addition, the findings emphasize the importance of adopting a holistic education framework that bridges the formal and non-formal education sectors while encouraging the active involvement of various stakeholders. The results of this research are critical to producing competent, innovative and future-ready individuals who are able to face the dynamic challenges of Era 5.0.